PENGEMBANGAN KETERAMPILAN ABAD KE-21 MELALUI PEMBELAJARAN IPS PADA MATERI GLOBALISASI SISWA KELAS VI SD (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social Studies (IPS) learning in elementary schools plays an important role in helping students develop 21st-century skills. This is especially evident in globalization topics, which are closely related to social change, technological development, and international relations. This study aims to examine how Social Studies learning can support the development of 21st-century skills among sixth-grade elementary school students, including critical thinking, creativity, communication, and collaboration. This research employs a literature review method by analyzing various scientific journals discussing Social Studies learning, globalization materials, and 21st-century skills. The findings indicate that 21st-century skills can be developed through the use of innovative learning models, such as Project-Based Learning, Problem-Based Learning, the integration of digital technology, and the use of interactive learning media. In addition, learning activities involving digital literacy, discussions, and problem-solving can enhance students’ critical thinking, creativity, and communication skills. Therefore, Social Studies learning on globalization topics can be an effective approach to developing 21st-century skills in elementary school students, particularly when implemented through engaging, active, and student-centered learning strategies.